ANALISIS SOSIAL, EKONOMI DAN BUDAYA DALAM PENGELOLAAN SANITASI MASYARAKAT PERMUKIMAN PESISIR KOTA KENDARI - Ira Ryski Wahyuni (UIN Sunan Gunung Djati Bandung, 2021)
Most of the coastal areas in Kendari City have developed into settlements that having poor sanitation conditions, practicing of open defecation free, using construction of latrines without the appropriateness of health standards, and some sanitation facilities built by Government is not functioning properly. This study wants to analyze the social, economic, and cultural aspects that affect the management of sanitation for coastal communities in Kendari City, consist of a description of community behavior, the level of knowledge, awareness, and participation of residents in sanitation, and the willingness and capacity to pay management fees for sanitation facilities in coastal settlements in Kendari City. The methodology of this research was a type of quantitative research with a survey method. The technique of collecting data was Simple Random Sampling. Based on the Slovin formula with a confidence level of 90% with a sample size of 218 households. The research location is in 9 sub-districts which are directly adjacent to the coast of Kendari City. This research shows that social, economic, and cultural aspects such as education level, occupation, income, community knowledge affect sanitation management in coastal.